Genomics in plant pathogen identification and control - Ogbuji, Nkechi Gloria; Agogbua, Josephine Udunma (Frontiers in Plant Science, 2025)
Recent advances in genomics have revolutionized plant pathogen detection and control by enabling faster and more accurate identification compared to traditional culture-based methods. Genomic tools like metagenomics and next generation sequencing (NGS) facilitate the detection of microorganisms (bacteria, fungi, viruses, and nematodes) directly from environmental samples. Genomics also provides information on plant-pathogen interactions, especially the detection of Resistance (R) genes and their role in plant defense against pathogens, aiding in the development of genetic markers for breeding disease-resistance crop species. Gene editing systems such as clustered regularly interspaced short palindromic repeats (CRISPR) associated protein 9 (CRISPR-Cas9), transcription activator-like effector nucleases (TALENs), and Zinc Finger nucleases (ZFNs) allow for precise genetic modification, either by incorporating a beneficial R genes or disabling susceptibility (S) genes of the host plant. RNA interference (RNAi) is another genomic tool used to suppress important pathogenic genes and inhibit disease development. Although the use of genomics in plant pathology is hampered by limitations such as high costs, complexity of data analysis and interpretation, and limited access to sequencing platforms, especially in developing countries, recent innovations and multi-disciplinary collaborations are tackling these issues. In general, genomics offers powerful tools that can be employed in the development of sustainable and effective plant disease management strategies, which will help to enhance crop protection and contribute to global food security.